1999
DOI: 10.1007/s001140050628
|View full text |Cite
|
Sign up to set email alerts
|

Precision of a Mammalian Circadian Clock

Abstract: This paper reports study of day-to-day instability in the locomotor activity rhythm of the nocturnal field mouse Mus booduga. The free-running period (tau) of this rhythm was estimated in constant darkness in n = 347 adult male mice. The "onset" and "offset" of locomotor activity rhythm were used as phase markers of the circadian clock. The precision of the onset of locomotor activity was observed to be a non-linear function of tau, with maximal precision at tau close to 24 h. The precision of the offset of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Several earlier studies reported correlation of circadian period with rhythm precision (a measure of intercycle period stability). They suggested that precision of circadian rhythms is high when the circadian period is closer to 24 h and decreases as period deviates from 24 h, but mostly at the organismal level and within the pacemaker SCN neurons [37][38][39][40][41][42]. In addition, we find that long circadian periods are largely noise driven as compared to short periods.…”
Section: Precision Of Circadian Rhythm Decreases With Increasing Periodmentioning
confidence: 56%
See 1 more Smart Citation
“…Several earlier studies reported correlation of circadian period with rhythm precision (a measure of intercycle period stability). They suggested that precision of circadian rhythms is high when the circadian period is closer to 24 h and decreases as period deviates from 24 h, but mostly at the organismal level and within the pacemaker SCN neurons [37][38][39][40][41][42]. In addition, we find that long circadian periods are largely noise driven as compared to short periods.…”
Section: Precision Of Circadian Rhythm Decreases With Increasing Periodmentioning
confidence: 56%
“…Reports by Aschoff [ 37 ] as well as Pittendrigh and Daan [ 38 ] led the latter to hypothesize that circadian rhythms are most stable as the endogenous period (τ) approaches 24 h, whereas deviation of τ from 24 h leads to reduction in rhythm stability and provided an evolutionary reasoning for such a hypothesis. This observation of rhythm stability being the lowest at a particular τ has since been substantiated by studies on various species [ 39 , 41 , 42 ], including the pacemaker SCN neurons [ 40 ], but others have reported either weak or absence of such trends [ 52 , 53 ]. To assess whether such correlation is observed mostly at the level of organisms and central pacemaker neurons or is a general property even for peripheral oscillator cells, we measured the intercycle variation in period across our clonal populations.…”
Section: Discussionmentioning
confidence: 80%
“…Since accuracy or precision of circadian clocks in assessing time in the local environment is likely to be closely related to fitness, it is critical to study its genetic variability in natural populations. Previous studies on wild-type animals with different clock periods reported a correlation between precision and circadian period (Pittendrigh and Daan, 1976; Sharma and Chandrashekaran, 1999); however, such a correlation was not seen in mutant strains of animals with distinctly different periods (Bittman, 2012). …”
Section: Introductionmentioning
confidence: 80%
“…The stability of circadian timekeeping in the face of fluctuating internal as well as external environments is likely to confer organisms with adaptive advantages (Daan, 2000). Therefore, precision of circadian clocks, which is key to their functioning as reliable timekeepers, is believed to be under the influence of selection pressures of the environment (Sharma and Chandrashekaran, 1999; Clodong et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, findings from some studies show association between circadian period close to 24 h and higher precision, suggesting that stability in circadian entrainment contributes to the evolution of circadian clocks in the face of cyclic fluctuations in nature [18]–[20]. To critically examine this, we carried out a laboratory selection study, where we imposed selection for adult emergence in a narrow window of time.…”
Section: Introductionmentioning
confidence: 99%